Benefits and challenges of energy efficient social housing. (September 2017) - Moore, Trivess; Nicholls, Larissa; Strengers, Yolande; Maller, Cecily; Horne, Ralph
Abstract: This paper presents a multi-method (interviews, cost-benefit analysis, technical monitoring) longitudinal evaluation of ten social housing dwellings in Horsham (Victoria, Australia), including four low-energy and six control houses. Occupants of the low-energy houses purchased 45-62% less electricity, had lower utility bills resulting in financial savings of $1, 050/year, had improved thermal comfort, health and social outcomes. However, there were several challenges for the providing government department and tenants, including supporting tenants to use certain sustainability features of the house as designed. The paper concludes by providing discussion to help guide similar projects in the future to more sustainable outcomes.